Establishment of a novel experimental model of infected anal fistula in rat - Zhao, Meng; Wang, Aitong; Zhang, Leisheng; Yu, Hao (Laboratory animal research, 2022)
Refractory Crohn's-like enterocutaneous fistula indicates the aggressive manifestation and lead to poor prognosis of patients. The development of multidisciplinary strategies for fistula administration largely subjects to the deficiency of animal model for disease remodeling and the underlying pathogenic mechanism. For the purpose, infected anal fistula model was conducted by BLV single-core electrolytic aluminum combined with dextran sodium sulfate. Notably, the inflammatory granulation tissue and inflammatory cell infiltration in the perianal tissue were arised on day 7 of the model by utilizing the Hematoxylin–eosin staining. With the aid of magnetic resonance imaging and signals of high-brightness. We intuitively observed the thickening and edema appeared in the fistula wall, which collectively suggested the formation of a fistula in the perianal area of the rat. Distinguish from the current models of anal fistula modeling including the body surface of fistula, backside of fistula and drainage wire of fistula, our model revealed multifaceted advantages such as quicker generation, higher modeling rate, preferable stability, better consistency, cost-effective, and in particular, more convenient to mimic clinical manifestations of anal fistula.